Skeletal effect of casein and whey protein intake during catch-up growth in young male Sprague–Dawley rats. Issue 1 (18th May 2016) - Masarwi, Majdi; Gabet, Yankel; Dolkart, Oleg; Brosh, Tamar; Shamir, Raanan; Phillip, Moshe; Gat-Yablonski, Galia
Abstract: The aim of the present study was to determine whether the type of protein ingested influences the efficiency of catch-up (CU) growth and bone quality in fast-growing male rats. Young male Sprague–Dawley rats were either fed ad libitum (controls) or subjected to 36 d of 40 % food restriction followed by 24 or 40 d of re-feeding with either standard rat chow or iso-energetic, iso-protein diets containing milk proteins – casein or whey. In terms of body weight, CU growth was incomplete in all study groups. Despite their similar food consumption, casein-re-fed rats had a significantly higher body weight and longer humerus than whey-re-fed rats in the long term. The height of the epiphyseal growth plate (EGP) in both casein and whey groups was greater than that of rats re-fed normal chow. Microcomputed tomography yielded significant differences in bone microstructure between the casein and whey groups, with the casein-re-fed animals having greater cortical thickness in both the short and long term in addition to a higher trabecular bone fraction in the short term, although this difference disappeared in the long term. Mechanical testing confirmed the greater bone strength in rats re-fed casein. Bone quality during CU growth significantly depends on the type of protein ingested. The higher EGP in the casein- and whey-re-fed rats suggests a better growth potential with milk-based diets. These results suggest that whey may lead to slower bone growth with reduced weight gain and, as such, may serve to circumvent long-term complications of CU growth.